Consequences of Different Pressures and Electrolytes on the Irreversible Expansion of Lithium Metal Half Cells. Issue 2 (16th December 2022) - Daubinger, Philip; Göttlinger, Mara; Hartmann, Sarah; Giffin., Guinevere A.
Abstract: Lithium metal is considered as the 'holy‐grail' among anode materials for lithium‐ion batteries, but it also has some serious drawbacks such as the formation of dendritic and dead lithium. In this study, the interplay of external pressure and different carbonate‐ and ether‐based electrolytes on the (ir)reversible expansion of lithium metal during cycling against lithium titanate and lithium iron phosphate is studied. In carbonate‐based electrolytes without any additives, lithium metal shows tremendous irreversible expansion and significant capacity reduction at elevated current densities due to the formation of mossy and dead lithium. The addition of fluoroethylene carbonate can reduce irreversible expansion and capacity reduction, especially when a high external pressure is applied. When an ether‐based electrolyte is used, the irreversible dilation of the lithium metal is suppressed when applying increased external pressures. Overall, increased external pressure appears to reduce the formation of mossy and dead lithium and improve the performance. Abstract : How external pressure impacts ? Cycling of lithium metal half cells revealed that an increased external pressure reduces the formation of dead lithium during cycling. Additionally, ether‐based electrolytes or carbonate‐based electrolytes with FEC as additive enhance the performance and reduce the formation of dead lithium in the cells.